Teachers' use of social media: exploring implications of interpersonal relations between teachers and middle school students in Turkey - Durgungoz, Ahmet (2018)
This is a qualitative study of the use of social media as a mediating agent between three teachers in Turkey and their students, whose age range was 12-15. This research was designed to discover how teachers’ communicative acts occur around three iconic social-media tools - YouTube, Google+ and WhatsApp. It also reports students’ understanding of such communicative acts as they influence the teacher/student relationship.